2018
DOI: 10.1002/hc.21467
|View full text |Cite
|
Sign up to set email alerts
|

Physical modification of carbon nanotubes with a dendrimer bearing terminal mercaptoundecahydrododecaborates (Na2B12H11S)

Abstract: The thiol‐substituted B12‐cluster mercaptoundecahydro‐closo‐dodecaborate Na2[B12H11SH] (BSH) was successfully attached to a poly(amido)amine (PAMAM) dendrimer, which contains a bis(decyloxy)decane core. The physical modification of single‐walled carbon nanotubes (SWCNTs) with dendrimer(SB12)4 afforded a SWCNT/dendrimer(SB12)4 nanohybrid that exhibited NIR‐I‐to‐NIR‐II fluorescence. Herein, we describe a promising strategy for in vivo imaging of boron clusters that may be widely applicable to boron neutron captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 62 publications
0
4
0
1
Order By: Relevance
“…As a method for the highly efficient delivery of boron drugs, investigations using liposomes [ 198 ], antibody modification [ 199 ], and dendrimers [ 200 ] have been reported. Kueffer et al reported that tumor accumulation could be improved by encapsulating BSH in liposomes and improving blood retention, but since BSH also accumulated in normal cells, a strategy to add tumor cell selectivity is necessary [ 201 ] Kang et al reported that BSH was efficiently taken up by cancer cells by encapsulating it in liposomes modified with a peptide that has a high affinity for integrin αvβ3, which is highly expressed in neovascularization and GBM [ 202 ].…”
Section: Relationship Between Boron Neutron Capture Therapy (Bnct) and Boron Compoundsmentioning
confidence: 99%
“…As a method for the highly efficient delivery of boron drugs, investigations using liposomes [ 198 ], antibody modification [ 199 ], and dendrimers [ 200 ] have been reported. Kueffer et al reported that tumor accumulation could be improved by encapsulating BSH in liposomes and improving blood retention, but since BSH also accumulated in normal cells, a strategy to add tumor cell selectivity is necessary [ 201 ] Kang et al reported that BSH was efficiently taken up by cancer cells by encapsulating it in liposomes modified with a peptide that has a high affinity for integrin αvβ3, which is highly expressed in neovascularization and GBM [ 202 ].…”
Section: Relationship Between Boron Neutron Capture Therapy (Bnct) and Boron Compoundsmentioning
confidence: 99%
“…By making a little associate of (SWCNT-C(CO)-[O(CH2)2]2-O-metallaborane], a single world carbon nanotube functionalized with Cobalt polaroid and graphene-oxide-close-do-deca-carbonate non-hydrides [30]. When these single-walled carbon nanotubes (SWCNT's) hybrid with dendrimer (SB12)4 contain the fluorescence of NIR-I/NIR-II [46]. That will prove boron clusters can be extensively usable in BNCT.…”
Section: 54mentioning
confidence: 99%
“…为3.12, 肿瘤内滞留时间超过48 h. SWCNT还具备荧光 成像性能 [212] . Yamagami等 [213] [199] ; (b) BPN示意图 [89] ; (c) Pcy示意图 [203] ; (d) MPEG-b-P(LA-co-D-Gal-MPCB)示意图 [204] (网络版彩图) . 在纳米医学的研究基础上, 含硼 量丰富(约50%)的氮化硼纳米材料是非常有潜力的纳…”
Section: 碳纳米材料unclassified